A Fleet Efficiency Factor for fleet size and mix problems using particle swarm optimisation. Issue 2 (4th May 2019) - Ehlers, Sören; Pache, Hannah; von Bock und Polach, Franz; Johnsen, Trond
ABSTRACT: Finding the optimal fleet composition under uncertainties is crucial for the economic success of a business. This paper presents the Fleet Efficiency Factor, a decision support tool for fleet size and mix problems and fleet composition problems. The method is based on a particle swarm optimisation algorithm combined with a stochastic model to include uncertainties into the decision-making progress. This combination allows selecting the best option out of a pool of available vessels, vehicles and aircrafts. Additionally, the FEF is based on the classical ship merit factor and thus capable of comparing different fleet compositions according to their economic efficiency, by describing the efficiency in a simple factor. A case study for the supply of an offshore platform in the high North is conducted. The approach proved to be flexible and applicable to different strategical and tactical planning problems in maritime transportation.